Alguns aspectos sobre a prática docente na década de 1970: o ensino colegial e a disciplina de matemática - Bento, Regina Thaíse Ferreira (2009)
The objective of this research is to investigate the teaching-staff practice in the high school during the reformulation movement of the mathematics teaching, occurred in Brazil between the years of 1960 and 1970, known as Modern- Mathematics Movement (MMM). To reach this aim were used in this research the legislations in force at that time, as Programas do Ensino Secundário, laid out by Portaria 966 on the 2nd of October 1951, besides the suggestion to follow a programmed instruction to the chair of Mathematics proposed by the group of Mathematics Teaching Study (GEEM), It was used also the volume I of the didactic collection books, entitled Mathematic-High School Modern Course (Matemática Curso Colegial Moderno), published in 1967 by Scipione Di Pierro Neto, Ruy Madsen Barbosa and Luiz Mauro Rocha. Besides that, It was used the student s notebook, who attended the first year of the high school in the year of 1970, and two interviews: one with the owner of the notebook and the other with the teacher who gave the classes of mathematic to this student. By comparison between the contents in the didactic book and the notebook, and the regulation established by legislation of the epoch. It was tried to understand the teaching-staff practice in the classroom. With that one got to the conclusion that teacher-practice study, cannot only be based on official documents